Clinical efficacy of stereotactic ablative radiotherapy for lung metastases arising from colorectal cancer. Issue 1 (December 2015) - Jung, Jinhong; Song, Si; Kim, Jong; Yu, Chang; Kim, Jin; Kim, Tae; Jeong, Seong-Yun; Kim, Su; Choi, Eun
Abstract Background Limited data describe the prognosis after stereotactic ablative radiotherapy for lung metastases arising from colorectal cancer. Thus, we evaluated treatment outcomes of stereotactic ablative radiotherapy for those patients. Methods The study involved patients received stereotactic ablative radiotherapy for one to three lung metastases arising from colorectal cancer at a single institution. A total dose of 40–60 Gy (median, 48 Gy) in three or four fractions was prescribed. Results A total of 79 metastatic lung lesions from 50 patients who underwent curative resection for their primary colorectal cancer or salvage treatment at a recurrent site were included. The one- and three-year local control rates were 88.7 % and 70.6 %, respectively. The three-year overall survival and progression-free survival rates were 64.0 % and 24.0 %, respectively. Patients with tumor volume ≤1.5 mL had a significantly better overall survival rate than those with tumor volume >1.5 mL (68.0 % vs. 60.0 % at three-year, p  = 0.02). Local control was associated with a trend towards better survival (p  = 0.06). No pulmonary complications greater than grade 2 were observed. Conclusion Stereotactic ablative radiotherapy is a competitive treatment modality for the management of lung metastases arising from colorectal cancer.